The origin and evolution of assessment criteria for persistent, bioaccumulative and toxic (PBT) chemicals and persistent organic pollutants (POPs). Issue 9 (1st August 2016) - Matthies, Michael; Solomon, Keith; Vighi, Marco; Gilman, Andy; Tarazona, Jose V.
Abstract : PBT and POP assessment criteria were developed from best science available from 1970 to 1990 and consensus-based policy discussions. Abstract : General public concern over the effects of persistent chemicals began in the early 1960s. Since then, significant scientific advances have increased our understanding of persistent, bioaccumulative, and toxic (PBT) chemicals and the properties and processes that influence their fates in, and adverse effects on, human health and the environment. In addition to the scientific advances, a number of legislations and agreements for national, international, and global identification and control of PBT chemicals have been adopted. However, some of the rationales and thoughts that were relied upon when the first criteria were developed to identify and categorize PBT chemicals and then POPs (persistent organic pollutants) have not been carried forward. Criteria have been based upon available data of neutral hydrophobic substances as reference chemicals, derived under laboratory conditions. They evolved over the last decades due to the diversification of the protection aims under various national regulatory frameworks and international agreements, advances in methods for estimation of physical/chemical properties, and the identification of chemicals which are non-traditional POPs. Criteria are not defined purely by science; they also are subject to the aims of policy. This paper offers a historical perspective on the development of criteria for PBT chemicals and POPs. It also offers suggestions for rationalization of protection goals, describes some emerging procedures for identification of compounds of concern, and proposes information that needs to be considered when applying criteria to screening and/or evaluation of new chemicals.